Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1099/jmm.0.000220
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of colonizing and invasive Staphylococcus aureus strains in northern Vietnam

Abstract: Staphylococcus aureus is an important global health problem worldwide. There is still scarce information on the population structure of S. aureus strains in Asia, where the majority of the world population lives. This study characterized the diversity of S. aureus strains in northern Vietnam through multilocus sequence typing (MLST). Eighty-five carriage isolates from the community and 77 invasive isolates from the clinical setting were selected and tested for meticillin resistance and the presence of Panton-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…Whether our findings are representative of all of China and adjacent countries remains to be addressed. Our findings do not support the previously indicated correlation of the PVL-positive ST59 subset (Taiwan clone) with infection ( 11 , 12 ). Thus, our study provides epidemiologic evidence challenging the widespread notion about a significant role of PVL in CA-MRSA dissemination in the ST59 lineage and in general.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Whether our findings are representative of all of China and adjacent countries remains to be addressed. Our findings do not support the previously indicated correlation of the PVL-positive ST59 subset (Taiwan clone) with infection ( 11 , 12 ). Thus, our study provides epidemiologic evidence challenging the widespread notion about a significant role of PVL in CA-MRSA dissemination in the ST59 lineage and in general.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies performed in Taiwan and northern Vietnam found a correlation between a PVL-positive subset of ST59 (Taiwan clone) and infection, but PVL-negative ST59 (Asia–Pacific clone) was found to be a largely noninfectious colonizer ( 11 , 12 ). Therefore, a causal relationship between PVL and infection has also been proposed for that CA-MRSA lineage.…”
mentioning
confidence: 99%
“…The previous report of ST59 was detected from a few MSSA isolates and in a single MRSA isolate in the United States, a large proportion of ST59 emerging in Taiwan was reported in 2004 and ST59-MRSA was called Taiwan clone [29]. ST59 was not only predominant in Shanghai [30], Guangzhou [31], and Taiwan [29], but also served as prevailing strains in Hongkong [32] and Vietnam [33]. The Asian Network for Surveillance of Resistant Pathogens (ANSORP) study conducted in 17 hospitals from Asian countries demonstrated that the predominant clones of CA-MRSA isolates were ST59-MRSA-SCCmec type IV-spa type t437 [34].…”
Section: Discussionmentioning
confidence: 99%
“…The Asian Network for Surveillance of Resistant Pathogens (ANSORP) study conducted in 17 hospitals from Asian countries demonstrated that the predominant clones of CA-MRSA isolates were ST59-MRSA-SCCmec type IV-spa type t437 [34]. These findings suggested that ST59 is currently spreading between adjacent regions and supporting its dominance in the Asian region as a whole [33]. It is widely assumed that the CA-MSSA isolates acquiring the resistance gene mecA would become the major sources of CA-MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria are very ubiquitous in the environment. Moreover, it colonizes approximately 30% of all humans—usually asymptomatically, however, any insufficiency of the host’s immune system poses a risk of infection development [2,3]. Due to the growing frequency of isolation of staphylococcal strains resistant to currently used antibiotics, their high virulence potential and common presence in environmental, there is an urgent need to search for new agents as well as therapy systems effective against these bacteria.…”
Section: Introductionmentioning
confidence: 99%